HEALTH BENEFITS OF FISH OIL - Qudrat Obidjonovich Abduhamidov; Firuza Farxodovna Ibragimova; Nargiza Jabborovna Ahmadaliyeva; Xodjimurodov Davron Ikramaliyevich (Modern American Journals, 2025)
Fish oil is a rich source of omega-3 fatty acids, which are essential polyunsaturated fats required for maintaining overall human health. These fatty acids, mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are widely recognized for their positive effects on cardiovascular, neurological, and musculoskeletal systems. Cardiovascular benefits include the reduction of triglyceride levels, lowering of blood pressure, and prevention of atherosclerosis, which collectively reduce the risk of heart diseases and stroke. In the nervous system, omega-3 fatty acids contribute to cognitive function, memory enhancement, and mood regulation, potentially reducing the risk of depression, anxiety, and neurodegenerative disorders like Alzheimer’s disease.In addition,fish oil exhibits anti-inflammatory properties that are beneficial for joint health, particularly in conditions such as rheumatoid arthritis and osteoarthritis. Supplementation with fish oil has been associated with decreased joint pain and stiffness, improving the quality of life for patients. Moreover, omega-3 fatty acids support ocular and dermatological health by maintaining visual acuity and skin hydration, and may also play a role in preventing age-related macular degeneration and dry eye syndrome.Dietary intake of fish or fish oil supplements provides a practical approach to incorporate these essential nutrients into daily life. Various clinical studies have demonstrated the efficacy and safety of fish oil consumption, highlighting its importance as a functional food and nutraceutical. Overall, fish oil is a valuable dietary supplement that promotes cardiovascular, neurological, musculoskeletal, ocular, and dermatological health, making it an important component of preventive medicine and health maintenance.
Keywords: Fish oil, Omega-3 fatty acids, Cardiovascular health, Cognitive function, Anti-inflammatory, Joint health, Skin health, Eye health, Nutraceuticals, Preventive medicine.